ENCOUNTERING STRANGE LAND: LIFE OF MIGRANTS IN ABDULRAZAK GURNAH’S THE LAST GIFT - Ashney, A Harrin; Sathiadevi, S Felicia Gladys (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Migrants have cross-cultural living experiences of their homeland and the host country. These migrants have a sense of belonging to countries and communities beyond their national borders. These migrants who cross national boundaries often find themselves in a state of great desperation and fear. Therefore, these displaced refugees experience fear of strangers, social isolation, and racial trauma. These asylum seekers overcome challenging and harmful situations and try to construct their own identities. Abdulrazak Gurnah is an East African of Tanzanian origin and works as a professor at Kent University in the UK. As a migrant, he deals with issues of belongingness, colonialism, displacement, memory, and migration in his writings. The Last Gift, Gurnah’s eighth novel sheds light on the traumatic experiences of displacement and struggles through his character Abbas, the protagonist, who has migrated from the East Coast of Africa to England. In his search for social space in a host land, his psychological depression, and his ethnic distress as a migrant writer, Gurnah graphically explores the complexities of his life in a strange land. This article focuses on encounters faced by the migrants as they try to relocate and construct an identity of their own in the strange land. It also focuses on the refugees’ ability to address the troubles they experienced and discovers the difficulties faced by first and second generation immigrants.